2012
DOI: 10.1097/sla.0b013e31824531ab
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Semiquantitative Terms in Surgery

Abstract: Laypersons overestimate probabilities of semiquantitative terms named by surgeons. We recommend using "percentages" or "odds ratios" to achieve a more reliable preoperative informed consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As presented by Gutknecht et al, patients do not fully comprehend the concept of a complication rate before surgery. 26 This could be an explanation for why patients may be easily persuaded to agree to a procedure that offers improved cosmesis while harboring increased complication rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented by Gutknecht et al, patients do not fully comprehend the concept of a complication rate before surgery. 26 This could be an explanation for why patients may be easily persuaded to agree to a procedure that offers improved cosmesis while harboring increased complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern is whether doubling the complication risk in surgeries that carry a 1–2 % complication risk can be considered ‘safe enough’ in order to be presented as a valid and equal option for patients. As presented by Gutknecht et al [27], patients do not fully comprehend the concept of a complication rate before surgery. This could be an explanation for why patients may be easily persuaded to agree to a procedure that offers improved cosmesis while harboring an increased complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, a low response rate can lead to a non‐responder bias and has the potential of creating a non‐representative sample. This can question the validity of the survey [33]. Surgical departments with a higher surgical volume were more likely to participate in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the decision making process on selecting the appropriate surgical treatment, discussions should be individualized to each patient as surgeons cannot broadly assume all patients will choose the scarless procedure. Gutknecht et al 31 reported that patients do not fully comprehend the concept of a complication rate before surgery. This explains why some patients may be easily persuaded to agree to a procedure that offers improved cosmesis, while potentially harboring an increased rate of complications.…”
Section: Discussionmentioning
confidence: 99%